Synthesis and characterization of novel polybenzimidazoles bearing pendant phenoxyamine groups - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
A novel aromatic diacid, 3, 5-dicarboxyl-4'-amino diphenyl ether, containing pendant phenoxy amine group was synthesized. Homo- and co-polybenzimidazoles containing different content of pendant phenoxyamine groups were synthesized by condensation of 3,3'-diaminobenzidine with this acid and a mixture of this acid and isophthalic acid in different ratio in polyphosphoric acid. Copolybenzimidazoles with structural variations were also synthesized based on this acid and pyridine dicarboxylic acid, terephthalic acid, adipic acid, or sebacic acid. The polymers have good solubility in polar aprotic solvents and strong acids and they form tough flexible films by solution casting. The polymers were characterized by different instrumental techniques (FTIR, TGA, DSC, XRD, etc.) and for solvent solubility, mechanical properties, inherent viscosity, and proton conductivity. The inherent viscosities of the polymers vary in the range of 0.62-1.52 dL/g. They have high thermal stability up to 475506 degrees C (IDT) in nitrogen, high glass transition temperatures (T-g) ranging from 313 to 435 degrees C and good tensile strength ranging from 58 to 125 MPa. Proton conductivity of homo polymer is 3.72 x 10(-3) S/cm at 25 degrees C and 2.45 x 10(-2) S/cm at 200 degrees C (c) 2008 Wiley Periodicals, Inc.
Keywords: Characterization; copolybenzimidazoles; High performance polymers; high temperature materials; pendant phenoxyamine group; polybenzimidazoles; synthesis

Polybenzimidazoles tethered with N-Phenyl 1,2,4-triazole units as polymer electrolytes for fuel cells - Potrekar, R. A.; Kulkarni, M. P.; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Polybenzimidazole (PBI) polymers tethered with N-phenyl 1,2,4-triazole (NPT) groups were prepared from a newly synthesized aromatic diacid, 3'-(4-phenyl-4H-1,2,4-triazole-3,5-diyl) dibenzoic acid (PTDBA). The obtained polymers show superior thermal and chemical stability and good solubility in many aprotic solvents. The inherent viscosities of all polymers were around 1 dL/g. They exhibit high thermal stability with initial decomposition temperature ranging from 515 to 530 degrees C, high glass transition temperature ranging from 375 to 410 degrees C, and good mechanical properties with tensile stress in the range of 66-98 MPa and modulus 1897-2600 MPa. XRD analysis indicates that these polymers are amorphous in nature. PhysicochemiCal properties such as water and phosphoric acid-uptake, oxidative stability, and proton conductivity of membranes of these polymers have also been determined. The proton conductivity ranged from 4.7 x 10(-3) to 1.8 x 10(-2) S cm(-1) at 175 degrees C in dry conditions. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2289-2303, 2009
Keywords: fuel cells; Polybenzimidazole; synthesis and characterization; Triazole

Nitrophenoxy groups containing polybenzimidazoles as polymer electrolytes for fuel cells: synthesis and characterization - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Applied Polymer Science, 2010)
Polybenzimidazoles containing different contents of pendant nitrophenoxy groups were prepared by condensation of 3,3'-diamino-benzidine with a mixture of 3,5-dicarboxyl-4'-nitro diphenyl ether and isophthalic acid (IPA) in different ratios in polyphosphoric acid. The polymers are soluble in polar aprotic solvents, they have inherent viscosities in the range of 0.75-1.10 dL g(-1) and they form tough and transparent films on solution casting. They have good thermal stability with initial decomposition temperature ranging from 380 to 416 degrees C in nitrogen, good tensile strength ranging from 56 to 65 MPa and reasonably good oxidative stability. Phosphoric acid uptake of these polymers is low compared with PBI and membranes doped with phosphoric acid exhibit good proton conductivity in the range of 6.6x 10(-3) to 1.9x 10(-2) S/cm at 25 degrees C and 1.2x 10(-2) to 4.9x 10(-2) S/cm at 175 degrees C, compared with 3.9x 10(-3) S/cm at 25 degrees C and 3.2x 10(-2) S/cm at 175 degrees C for PBI. These membranes are suitable for applications as polymer electrolyte for fuel cell and presumably for gas separation at high temperature. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 3282-3292, 2010
Keywords: Characterization; membranes; pendant nitrophenoxy group; polybenzimidazoles; proton conductivity; synthesis